From graphemes to morphemes: An alternative way to improve skills in children with dyslexia - Traficante, Daniela (Revista de Investigación en Logopedia, 2012)
This contribute provides a review of the main research data and models that can guide training interventions in the case of reading difficulties. In particular, the paper is focused on evidence concerning the role of morphemic constituents in word recognition and reading aloud. Data from children with and without dyslexia show the usefulness of morphemic parsing to improve fluency and comprehension. The results are interpreted in the light of Grainger & Ziegler’s (2011) proposal. It can be considered an interesting framework to model reading processes, as it offers an integrate view of reading acquisition, in which even morphological awareness can play an important role along with orthographic and phonological components. Some examples of training interventions aimed at improving the use of morphemic constituents in children with reading difficulties are presented and discussed.
Keywords: Morphology; Reading acquisition; Reading models.